Perinatal effects of premature rupture of membranes - Mere, Juan (2015)
OBJECTIVES: To determine the maternal characteristics with statistical probabilities of association with neo natal infection in patients rum premature rupture of membranes (PROM), both at term, as premature. Evaluate the perinatal morbidity and mortality MATERIAL AND METHODS: Retrospective observational study, case-control (infected-no newborn infected) between April 1998 and March 1999, according to protocol established in the Department of Obstetrics Loayza Hospital, entering pregnant with a single fetus, active, without fever and diagnosed with RPM. RESULTS: Of 3985 deliveries, 284 had RPM: 263 were to term and 21 preterm; 8 infants were not assessed (transferred by malformations, four mature, four premature). 259 pregnancies to term 42 infants were infected (16.2%) and 17 premature 11 were infected (64.7%). In term pregnancies, unmarried marital status was statistically significant in cases; prenatal care was not decisive for neonatal infection. Risk of neonatal infection at term for more than 6 hours (when they exceed the maximum 24 hours); cesarean section was significantly higher in cases (47.6%) - (controls: 29.9%). Over 60% of all pregnancies had preterm cesarean. The Apgar indices were significantly lower in cases (at term and preterm mainly); also they were lower in preterm cases vs mature cases. In preterm pregnancies there were two deaths and a live infant died of extreme prematurity. CONCLUSIONS: is single, RPM time after six hours (maximum over 24 hours).